PO-52 - Effect of tissue factor expression by colorectal cancer on cancer stem cell activity. Issue 140 (April 2016) - Clouston, H.W.; Lamb, R.; Duff, S.; Kirwan, C.C.
Abstract : Introduction: Abnormal Tissue factor (TF) expression occurs in many cancers including colorectal and is associated with a poor prognosis. TF expression promotes cancer stem cell (CSC) activity in breast and squamous cell carcinoma (SCC). Aim: The aim of the research is to determine the effect of TF expression by colorectal cancer cell lines on colorectal CSC activity. Materials and Methods: Colorectal cancer cell lines with high (DLD-1) and low (SW620) TF expression were stably transduced to knock down (TF-ve) and over express (TF + ve) TF. CSC activity was assessed using the cancer sphere assay (sphere forming efficiency (SFE) = spheres formed / cells plated) and by ALDH1 expression (by florescent activated cell sorting). When comparing transduced cells to their control the ALDH1 expression was normalised to their control. Results: The naturally high TF expressing cell line (DLD-1) compared to the low TF expressing cell line (SW620) had a reduced SFE (0.7 (SD 0.39) vs 1.38 (SD 0.68), p < 0.05) and less cells expressed ALDH1 (15.3% (SD 1.2) vs 26.9% (SD 2.1), p = 0.02). DLD-1 TF + ve compared to its control had a reduced SFE (0.33 (SD 0.14) vs 0.66 (SD 0.42), p < 0.01) and less cells expressed ALDH1 (0.72 (SD 0.069) p = 0.001) (normalised to negative control). There was no difference in SFE (1.21 (SD 0.56) vs 1.29 (SD 0.50) p = 0.4) and ALDH1 expression (0.81 (SD 1.00) p = 0.5) between SW620 TF + ve and its control. DLD-1 TF-ve and SW620 TF-ve had increased SFE compared to their controls (DLD-1: 0.63 (SD 0.27) vs 0.41 (SD 0.35) p < 0.01; SW620: 2.03 (SD 0.86) vs 1.21 (SD 0.70) p < 0.01), and increased ALDH expression (DLD-1: TF-ve 1.23 (SD 0.74)p = 0.04 and SW620: TF-ve 1.31 (SD 0.08) p < 0.001 normalised to controls). Conclusions: Unlike in breast and SCC, in colorectal cancer cell lines TF inhibits CSC activity. This has significance if anti-tissue factor treatments are considered as an anti-cancer treatment as this may increase the cancer stem cell activity.